BAHASA MELAYU DALAM SUDUT PANDANG REMAJA SUKU MELAYU DI BATAM - Mubarak, Zia Hisni; Aldriani, Yessie (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The objective of this study aimed at knowing the perspective of Malay’s teenagers towards their own language in Batam. Malay language is a unique language where mostly Bahasa Indonesia is taken from it. This study is important to be conducted since the preservation issue of local culture, including its language, arrises as the main concern. The study used qualitative method where to collect the data some informants were needed to provide the information about their own perspective toward their language. Those informants are the teenagers of Malay who are living in Batam, Riau Islands Province. The researcher collected the data by using interview and record it by using video camera or voice note. Some questions were asked during the session to some Malay’s teenagers. There were four questions answered by the informants and they showed a good point of view from Malay’s teenagers towards their own language and culture. The study revealed that the teenagers were proud of their local identity including language and culture. Keywords— Malay language, teenagers’ perspective, Batam’s Malay.  Abstrak— Tujuan dari penelitian ini bertujuan untuk mengetahui perspektif remaja Melayu terhadap bahasa mereka sendiri di Batam. Bahasa Melayu adalah bahasa yang unik di mana sebagian besar orang Indonesia diambil darinya. Studi ini penting dilakukan karena masalah pelestarian budaya lokal, termasuk bahasanya, muncul sebagai perhatian utama. Penelitian ini menggunakan metode kualitatif di mana untuk mengumpulkan data beberapa informasi diperlukan untuk memberikan informasi tentang perspektif mereka sendiri terhadap bahasa mereka. Informan tersebut adalah remaja Melayu yang tinggal di Batam, Provinsi Kepulauan Riau. Peneliti mengumpulkan data dengan menggunakan wawancara dan merekamnya dengan menggunakan kamera video atau catatan suara. Beberapa pertanyaan diajukan selama sesi kepada beberapa remaja Melayu. Ada empat pertanyaan yang dijawab oleh informan dan mereka menunjukkan sudut pandang yang baik dari remaja Melayu terhadap bahasa dan budaya mereka sendiri. Studi ini mengungkapkan bahwa para remaja bangga dengan identitas lokal mereka, termasuk bahasa dan budaya.. Kata Kunci— Bahasa Melayu, perspektif remaja, Bahasa Melayu Batam.